Fablehaven. [Book 3], Grip of the shadow plague - Mull, Brandon, 1974- (Mull, Brandon, 1974- Fablehaven, 2008)
After defeating one enemy and unveiling a traitor, Kendra and Seth plunge into the international world of magic. As Kendra travels to another refuge to locate an artifact of incredible strength, Seth faces another attack at Fablehaven. The creatures there are turning, not falling into evil like the fairies previously but actually turning into shadow-- evolving into powerful and more threatening forms never seen before. Even those creatures known to be resistant to falling are changing and infecting those around them.